(untitled) (Nepal Journal of Neuroscience, 2026)
Background: Severe traumatic brain injury remains associated with substantial morbidity and mortality despite neurosurgical advances. Gut dysbiosis following traumatic brain injury has been implicated in poor outcomes, and probiotics have shown variable effects in mitigating this issue. Objective: To determine the effect of probiotic supplementation on mortality and time to death among patients with severe traumatic brain injury. Methods: This double-blind, prospective, randomized controlled trial included 54 adult patients: 27 received probiotics with early enteral feeding, and 27 received early enteral feeding alone (control group). All patients received standard traumatic brain injury care. Outcomes assessed included clinical status using the Glasgow Outcome Score Extended, lengths of stay, complications, mortality rates, and time to death. Results: Favorable outcomes at discharge did not differ significantly between the intervention (29.6%) and control groups (18.5%) (p=0.244). A paradoxical finding was however observed: while the median survival time (time to event/death) was significantly longer for the probiotics group (16.0 days, 95% confidence interval: 6.4 to 25.6) compared to the placebo group (5.0 days, 95% confidence interval: 0.2 to 9.8) (log-rank p=0.002), the overall 30-day mortality rate was significantly higher in the probiotic group (22.2%) than in the control group (11.1%) (p=0.033). Conclusion: Probiotic supplementation resulted in a higher 30-day mortality rate in patients with severe traumatic brain injury, despite delaying the time to mortality among those who died. This contradictory outcome represents a significant safety signal that warrants further investigation into the use of probiotics in this critically ill population.